Soil N2O fluxes and related processes in laboratory incubations simulating ammonium fertilizer depots. (January 2017) - Deppe, Marianna; Well, Reinhard; Giesemann, Anette; Spott, Oliver; Flessa, Heinz
Abstract: High concentrations of ammonium (NH4 + ) in soil have been shown to inhibit nitrification, and fertilizer injection as conducted during CULTAN (controlled uptake long-term ammonium nutrition) management might thus have the potential to reduce N2 O emission from arable soil. We conducted an incubation experiment with different NH4 + concentrations in soil that resembled concentrations as expected at and around injection spots (5000, 2250, 1000, 450, 0 mg NH4 + -N kg −1 soil) directly after fertilization and after dilution due to plant uptake or precipitation. N2 O emission was measured in dynamic soil mesocosms over a period of 21 days. Acetylene inhibition and 15 N tracer approaches were used to calculate the relative contribution of nitrification and denitrification to N2 O emission. An isotopomer approach was applied to gain further insight into N2 O producing processes. We expected lower contribution of nitrification-derived N2 O to total N2 O emission and a higher N2 O/NO3 − ratio from nitrification with increasing NH4 + levels. Nitrification indeed declined with increasing NH4 + level, and no nitrification occurred in the 5000 mg NH4 + -N kg −1 soil treatment. A pool dilution approach showed that gross nitrification in 450 mg NH4 + -N kg −1 soil (nitrification rate: 4.96 mg NO3 − -N kg soil d −1 ) was by a factor of 2.6 and 6 higher than in 1000 and 2250 mg NH4 + -N kg −1 soil treatments. In the 5000 mg NH4 + -N kg −1 soil treatment, gross nitrification occurred at very small rates (0.1 mg NO3 − -N kg soil d −1 ). Similarly, N2 O emission declined with increasing NH4 + level. The N2 O yield of nitrification was between 0.07 and 0.15% of NO3 − production, but was not affected by increasing NH4 + level. Nitrification was the dominant source of N2 O throughout the incubation at all NH4 + levels, and there was no significant change in the relative contribution of nitrification and denitrification with NH4 + level or time. This finding indicates that denitrification derived N2 O emissions were similarly reduced at high NH4 + levels. Applying the non-equilibrium technique to our 15 N tracer data revealed heterogeneous distribution of denitrification in soil, with at least two distinct NOx − (NO3 −  + NO2 − ) pools and spatial separation of NOx − formation and consumption. The isotopomer approach provided reasonable results in comparison with the acetylene inhibition and 15 N tracer approaches and indicated substantial contribution of nitrifier denitrification and/or coupled nitrification-denitrification (10–40%) to total N2 O production. Highlights: Inhibition of nitrification at NH4 + concentrations occurring in fertilizer depots. Heterogeneous distribution of denitrification revealed by 15 N tracer application. SP and δ 18 O isotopomer approach indicate substantial nitrifier denitrification. N2 O yield of nitrification unaffected by increasing NH4 + level.